Community Empowerment through Entrepreneurship and Financial Management Training for SMEs - Muzayyanah Yuliasih; Lia Nurina; Wahyu Purwandari; Rina Destiana; Muh. Zulfi Qadri (PT. Global Research Collaboration, 2024)
The community service program titled